Towards real-time event-based communication in mobile ad hoc wireless networks. - CAHILL, VINNY (My University, 2003)
Most previous work on real-time event-based communication has assumed infrastructure-based networks. The underlying assumption of this work is that application components are stationary and that a fixed network infrastructure exists to facilitate communication between them [1]. Ad hoc wireless networks comprise sets of mobile nodes connected by wireless links that form arbitrary wireless network topologies without the use of any centralized access point. Ad hoc wireless networks are inherently self-creating, selforganizing and self-administering [2]. Such highly mobile, dynamic networks do not satisfy the design assumptions for previous real-time event-based communication.
Proceedings of 2nd International Workshop on Real-Time LANS in the Internet Age (ECRTS/RTLIA'03),
2nd International Workshop on Real-Time LANS in the Internet Age
PUBLISHED
Keywords: Computer Science